Customer Experience as the Driving Force for Supply Chains Digital Transformation - Nowicka, Katarzyna (European Journal of Economics and Business Studies, 2020)
Supply chain managers constantly look for the resources that are able to enhance and improve supply chain competitiveness. This competitiveness is analysed mainly in the light of cost, time and quality of the customers’ service delivered by the supply chain management. Today one of the most important resource impacting on driving business in the competitive way are the digital technologies. This is mainly due to the fact that digital technologies are strongly changing the innovation level of the company and its performance. Therefore it is worth to analyse the influence of digital technologies on supply chain competitiveness in terms of cost, time and quality. The aim of this paper is to present the most important areas that are impacted by the digital technologies in improving of supply chain competitiveness. The results of the empirical research, conducted among 120 supply chain managers in 2018, show that the aspect of quality is the weakest point in terms of digital innovation impacting on supply chain competitiveness. Thus in the second part of the paper the analyses of the role of the customers experience have been done to understand the new approach to the role of digital technologies. The digital innovation is impacting the whole customers’ journey during their relation not only with the company, but with the supply chain – that is actually the organization of several independent companies. In this way digital technologies starting to be a central point of supply chain configuration for improving its competitiveness.
Keywords: Supply Chain Digital Transformation, Customer Experience, Customer Journey, Digital Innovation, Supply Chain Competitiveness